PERBAIKAN KUALITAS LAYANAN UNTUK MENINGKATKAN KEPUASAN DAN LOYALITAS KONSUMEN DENGAN METODE SERVQUAL DAN STRUCTURAL EQUATION MODELING (SEM) DI MIROTA, SURABAYA - Limantoro, Sharleen Ekaputri; Surjani, Rosita Meitha; Hadiyat, M. Arbi (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Retail is a business opportunity that is widely used by entrepreneurs so thatbusiness competition among retail businesses is tight. Therefore, retailers need todo efforts in order to survive. In this research the retail discussed is Mirota. Mirotais a retail store that sells a various products of typical Indonesian culture.Everyday, Mirota is visited by many customers from domestic and foreigncountries travelling to Surabaya so that its existing problems are often consumercomplaints. Based on existing problems, Mirota needs improving the servicequality. The improvement of service quality to increase customer satisfaction andconsumer loyalty was conducted by using SERVQUAL method and StructuralEquation Modeling (SEM). The purpose of this research is to measure andevaluate the causes of service quality discrepancies, to know the relationshipbetween service quality, customer satisfaction, and customer loyalty, and topropose proposal improvements. The gained results from this research was a gap5 on quality of service at Mirota. The gap was caused by the gaps 1, 2, and 4.Quadrant analysis performed to determine the weaknesses of the company werebased on the comparison of the level of expectations and consumer perceptions.The results of measurements of the relationship quality of service, customersatisfaction and customer loyalty were found that there was the influence ofservice quality on customer satisfaction by 0.499, the effect of customersatisfaction on customer loyalty at 0.66, but there was no significant effect ofservice quality on customer loyalty. The results of the analysis slices quadrant IVand the close relationship between the model used as a reference in determiningimprovement using by Quality Function Deployment (QFD). From the QFDresults, the main improvement was done by looking at the importance of how thevalue of more than 245.4. Improvements are doing market research, providingparking directions and updating parking system with the valley system, givinggoods directions and arranging the goods.